Potential Barriers of Patient Involvement in Health Technology Assessment in Central and Eastern European Countries - Dimitrova, Maria; Jakab, Ivett; Mitkova, Zornitsa; Kamusheva, Maria; Tachkov, Konstantin; Nemeth, Bertalan; Zemplenyi, Antal; Dawoud, Dalia; Delnoij, Diana M. J.; Houýez, François; Kalo, Zoltan (Frontiers in Public Health, 2022)
Patients' perspectives are important to identify preferences, estimate values and appreciate unmet medical needs in the process of research and development and subsequent assessment of new health technologies. Patient and public involvement in health technology assessment (HTA) is essential in understanding and assessing wider implications of coverage and reimbursement decisions for patients, their relatives, caregivers, and the general population. There are two approaches to incorporating the patients' voice in HTA, preferably used in a mix. In the first one, patients, caregivers and/or their representatives directly participate at discussions in different stages of the HTA process, often at the same table with other stakeholders. Secondly, patient involvement activities can be supported by evidence on patient value and experience collected directly from patients, caregivers and/or their representatives often by patient groups Patient involvement practices, however, are limited in Central and Eastern European (CEE) countries without clear methodology or regulatory mechanisms to guide patient involvement in the HTA process. This poses the question of transferability of practices used in other countries, and might call for the development of new CEE-specific guidelines and methods. In this study we aim to map potential barriers of patient involvement in HTA in countries of the CEE region.